Industrial training report: Perpustakaan Tengku Anis / Nila Arofa’ina - Arofa’ina, Nila (Perpustakaan Tengku Anis, 2023)
Internship is a course that students must do in the form of practice to apply the knowledge that has been obtained during college. By doing an internship, students can find out how far they understand the knowledge they get. In this report, students report the results of an internship that has been carried out for four months at the Tengku Anis Library, UiTM Cawangan Kelantan Machang Campus. In their internship practice, students have learned in all units in the library. In addition to conducting internship activities within the library, students also participated in external activities organized by Tengku Anis Library, UiTM Cawangan Kelantan Machang Campus.